Hybrid Fluid-borne Noise Control in Fluid-filled Pipelines. (September 2016) - Pan, M; Johnston, N; Plummer, A
Abstract: This article reports on an initial investigation of a hybrid fluid-borne noise control system in hydraulic pipelines. The hybrid system is built by integrating an active feedforward noise controller with passive tuned flexible hoses. The active attenuator is designed to cancel the dominant harmonic pressure pulsations in the fluid line, while the passive hose is tuned to attenuate the residual high frequency pulsations. The active attenuator can effectively decrease the fluid-borne noise by superimposing a secondary anti-phase control signal. Adaptive notch filters with the filtered-X least mean square algorithm were applied for the controller and a frequency-domain least mean square filter was used for the secondary path on-line identification. The transmission line model was used to model the pipeline, and a time-domain hose model which includes coupling of longitudinal wall and fluid waves was used to model the flexible hose. Simulation results show that very good noise cancellation was achieved using the proposed approach, which has several advantages over existing fluid-borne noise control systems, being effective for a wide range of frequencies without impairing the system dynamic response much. While the flexible hoses may be less effective than purpose-built passive silencers, they can form an inexpensive and practical solution in combination with active control.